HUBUNGAN KADAR HEMOGLOBIN (HB) DENGAN LAMA PERSALINAN KALA II PADA IBU BERSALIN DI PMB NY SUTINI DESA JATIROTO UTARA KABUPATEN JEMBER - Tri Rahayu Retna Ningtiyas; Iit Ermawati; Yessy Nur Endah Sary (NHM PRESS, 2023)
Hemoglobin level is one hematological parameter that changes during pregnancy. Low hemoglobin levels result in prolonged labor in the second stage. The aim of this study was to analyze the correlation between hemoglobin levels and the duration of the second stage of labor. This study used an observational analytic design with a cross-sectional approach. Data were taken from observation sheets which were carried out from May to June 2023 with a population are 40 mothers giving birth and a sample are 36 respondents using an accidental sampling technique. Data collection includes coding, editing, and tabulating. Bivariate analysis using the product-moment correlation test showed a p-value = 0.000 <α 0.05, meaning that there was a correlation between hemoglobin levels and the duration of the second stage of labor. With a correlation value of -0.78. This means that the lower the hemoglobin level, the longer the second stage of labor. Suggestions put forward, by research sites should check hemoglobin levels in the first and third trimesters of pregnancy so that risk factors can be detected early in pregnancy.